Distribution of races of Pyrenophora tritici-repentis in Algeria and identication of a new virulence type - BENSLIMANE, Hamida; LAMARI, Lakhdar; BENBELKACEM, Abdelkade; SAYOUD, Rachid; BOUZNAD, Zouaoui (Phytopathologia Mediterranea, 2011)
Tan spot, caused by Pyrenophora tritici-repentis, is a foliar disease of wheat, responsible for high economic losses in several wheat growing areas in the world. There are eight known races of P. tritici-repentis based on ability to induce necrosis and/or chlorosis on a set of differential cultivars. Fifty five isolates of P. tritici-repentis originating from diverse wheat growing regions in Algeria were studied to determine which races are present and to identify new races. Races 1, 4, 5, 6, 7 and 8 were found and a new virulence pattern was identified. Isolates with this pattern induced necrosis in durum wheat but failed to induce any disease in the common wheat genotypes in the differential set.